2018
DOI: 10.3892/etm.2018.7048
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous injection of post‑hemorrhagic shock mesenteric lymph induces multiple organ injury in rats

Abstract: Post-hemorrhagic shock mesenteric lymph (PHSML) has an important role in the multiple organ injuries caused by severe shock. The current study investigated whether intravenous injection of PHSML induces organ injury in normal rats. Following the establishment of hemorrhagic shock in donor rats (40±2 mmHg, 3 h), PHSML was drained during hypotension at 1-3 h and then injected to normal rats through the femoral vein within 30 min. The mean arterial pressure (MAP) was measured, and samples were obtained for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Trypsin, a proteolytic enzyme released from damaged cells, can lead to excessive protein catabolism and aggravation of cellular damage. [ 28 ] Zhao et al [ 29 ] found that injecting post-HS mesenteric lymph (PHSML) from rats into the veins of normal rats could significantly increase trypsin activity in plasma, suggesting that toxic components in PHSML cause damage to cells and increase the release of trypsin.…”
Section: Bioactive Substancesmentioning
confidence: 99%
“…Trypsin, a proteolytic enzyme released from damaged cells, can lead to excessive protein catabolism and aggravation of cellular damage. [ 28 ] Zhao et al [ 29 ] found that injecting post-HS mesenteric lymph (PHSML) from rats into the veins of normal rats could significantly increase trypsin activity in plasma, suggesting that toxic components in PHSML cause damage to cells and increase the release of trypsin.…”
Section: Bioactive Substancesmentioning
confidence: 99%
“…It should be pointed out that the present study did not demonstrate the correlation of PHSML inducing lung injury and autophagy in healthy rats. However, our previous experiment showed that intravenous injection of PHSML-induced lung injury in healthy rats (4), and the current experiment showed that PHSML altered autophagy marker protein expressions in PMVECs in vitro , and demonstrated that PHSML induced lung injury through autophagy at the cellular level. These results specified the relationship between PHSML and autophagy during hemorrhagic shock ALI.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, exploring effective prevention and treatment measures for ALI has positive significance to reduce the morbidity and mortality caused by severe hemorrhagic shock. Posthemorrhagic shock mesenteric lymph (PHSML) return involves in the development and progression of ALI (3)(4)(5), and suggesting that measures targeting PHSML is essential for the intervention of hemorrhagic shock-induced ALI. Studies have shown that 17-β estradiol (E2) treatment reduced hemorrhagic shock-induced organ injury, improved mesenteric lymphatic vascular contractile function and vascular reactivity, and restored cellular immune function (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…[20] Rats are widely used as experimental animals to study the GL in lymph-related research. [21] In previous studies, [22] the rats were fasted for 6-12 hours pre-operation; however, the rats were not fasted in the current study. The lack of fasting did not affect our experimental process but instead made it smoother, possibly because more GLF was produced by enriching the gut-blood circulation, and more GLF was drained per unit time, which was more conducive to our experiments.…”
Section: Discussionmentioning
confidence: 80%